Visual and Anatomical Outcomes of Early versus Delayed Vitrectomy in Diabetic Vitreous Hemorrhage - Muhammad Usman Zia, Mahtab Haider, Ahmad Mustafa, Mahwish Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic vitreous hemorrhage (VH) is a major cause of sudden vision loss in patients with proliferative diabetic retinopathy (PDR). Objective: To compare the visual and anatomical outcomes of early versus delayed pars plana vitrectomy in patients presenting with diabetic vitreous hemorrhage. Methods: This comparative interventional study was conducted at Lahore General Hospital, Lahore from September 2022 to February 2023, including 185 patients diagnosed with diabetic vitreous hemorrhage. Patients were divided into two groups: Group A underwent early vitrectomy within six weeks of hemorrhage onset, and Group B underwent delayed vitrectomy after six weeks of observation. All patients underwent 25-gauge PPV with intraoperative panretinal photocoagulation (PRP). Best-corrected visual acuity (BCVA) was measured preoperatively and at one, three, and six months postoperatively. Results: Among 185 patients, 92 underwent early and 93 underwent delayed vitrectomy. The mean age was 54.3 ± 8.7 years in the early group and 55.8 ± 9.2 years in the delayed group. At six months, mean postoperative BCVA improved from 1.88 ± 0.24 to 0.68 ± 0.19 logMAR in the early group and from 1.85 ± 0.27 to 0.91 ± 0.23 logMAR in the delayed group (p < 0.001). Anatomical success was achieved in 97.8% of early cases and 91.4% of delayed cases (p = 0.06). Recurrent vitreous hemorrhage occurred in 10.9% of early cases and 22.6% of delayed cases (p = 0.03). The mean operative time was significantly shorter in the early group (64.2 ± 11.3 vs. 79.6 ± 14.7 minutes; p < 0.001). Conclusion: It is concluded that early vitrectomy provides better visual recovery, faster rehabilitation, and fewer postoperative complications compared to delayed vitrectomy in diabetic vitreous hemorrhage. Keywords: Diabetic vitreous hemorrhage, Early vitrectomy, Delayed vitrectomy, Pars plana vitrectomy, Visual outcomes